2019
DOI: 10.1158/0008-5472.can-18-2003
|View full text |Cite
|
Sign up to set email alerts
|

Acetylation of CCAR2 Establishes a BET/BRD9 Acetyl Switch in Response to Combined Deacetylase and Bromodomain Inhibition

Abstract: There continues to be interest in targeting epigenetic "readers, writers, and erasers" for the treatment of cancer and other pathologies. However, a mechanistic understanding is frequently lacking for the synergy observed when combining deacetylase and bromodomain inhibitors. Here we identify cell cycle and apoptosis regulator 2 (CCAR2) as an early target for acetylation in colon cancer cells treated with sulforaphane. N-terminal acetylation of CCAR2 diminished its interactions with histone deacetylase 3 and b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(73 citation statements)
references
References 54 publications
(86 reference statements)
1
72
0
Order By: Relevance
“…Acetylation of CCAR2 on Lys54/97 induced by HDACI sulforaphane (SFN) diminished its interactions with HDAC3 and β-catenin. Treatment with the BET (acetyl-lysine reading proteins) inhibitor JQ1 synergized with SFN suppressed tumor development effectively in a preclinical model of colorectal cancer (79). Another study identified that once Lys112 and Lys215 on CCAR2 were acetylated by MYST family HAT hMOF, the interaction of CCAR2-SIRT1 was suppressed, resulting in an increased activity of SIRT1, which further deacetylated CCAR2 to stabilize the SIRT1-CCAR2 complex.…”
Section: Homologous Recombinationmentioning
confidence: 99%
“…Acetylation of CCAR2 on Lys54/97 induced by HDACI sulforaphane (SFN) diminished its interactions with HDAC3 and β-catenin. Treatment with the BET (acetyl-lysine reading proteins) inhibitor JQ1 synergized with SFN suppressed tumor development effectively in a preclinical model of colorectal cancer (79). Another study identified that once Lys112 and Lys215 on CCAR2 were acetylated by MYST family HAT hMOF, the interaction of CCAR2-SIRT1 was suppressed, resulting in an increased activity of SIRT1, which further deacetylated CCAR2 to stabilize the SIRT1-CCAR2 complex.…”
Section: Homologous Recombinationmentioning
confidence: 99%
“…They are the only domains, which bind specifically to histone acetylation marks (Jain & Barton, 2017). Even though combined treatment with HDAC and BET inhibitors (BETi) revealed additive or synergistic effects in several cancer entities, such as cutaneous T-cell lymphoma, neuroblastoma, glioblastoma, non-small cell lung cancer, adenocarcinoma, and colon cancer (Mazur et al, 2015;Shahbazi et al, 2016;Adeegbe et al, 2017;Meng et al, 2018;Rajendran et al, 2019;Zhao et al, 2019), so far only few studies described the mono-and combined treatment options with BETis in GCTs. Even though combined treatment with HDAC and BET inhibitors (BETi) revealed additive or synergistic effects in several cancer entities, such as cutaneous T-cell lymphoma, neuroblastoma, glioblastoma, non-small cell lung cancer, adenocarcinoma, and colon cancer (Mazur et al, 2015;Shahbazi et al, 2016;Adeegbe et al, 2017;Meng et al, 2018;Rajendran et al, 2019;Zhao et al, 2019), so far only few studies described the mono-and combined treatment options with BETis in GCTs.…”
Section: Hdac Inhibitors Plus Bromodomain Protein Inhibitorsmentioning
confidence: 99%
“…Recently, the anti-cancer efficacy of inhibitors against the bromodomain and extra-terminal domain-containing (BET) protein family have been evaluated in several cancers, such as prostate, breast, colon, intestine, pancreas, liver, lung, brain, oral squamous cell carcinoma, and leukemias (Sahai et al, 2016;Saenz et al, 2017;Xu & Vakoc, 2017;Sahni & Keri, 2018;Zhang et al, 2018;Baldan et al, 2019). Even though combined treatment with HDAC and BET inhibitors (BETi) revealed additive or synergistic effects in several cancer entities, such as cutaneous T-cell lymphoma, neuroblastoma, glioblastoma, non-small cell lung cancer, adenocarcinoma, and colon cancer (Mazur et al, 2015;Shahbazi et al, 2016;Adeegbe et al, 2017;Meng et al, 2018;Rajendran et al, 2019;Zhao et al, 2019), so far only few studies described the mono-and combined treatment options with BETis in GCTs. The amount of transcripts of bromodomain-containing genes increases the higher the GCT stage is (Gashaw et al, 2005), indicating bromodomains being an interesting target for GCT treatment.…”
Section: Hdac Inhibitors Plus Bromodomain Protein Inhibitorsmentioning
confidence: 99%
“…Thus, Nrf2 exerted an apparent oncogenic role in the gut, and Nrf2 status dictated Hdac inhibitory responses to sulforaphane and the extent of tumor growth suppression [164]. Another interesting avenue is the synergistic combination of sulforaphane with the BET inhibitor JQ1 in colon cancer models, targeting the non-histone protein Cell cycle and apoptosis regulator 2 (CCAR2) for acetylation and altered Wnt coactivator functionality [165]. As BET proteins are reported to interact with and inhibit NRF2 [44], the prospect of combined deacetylase and bromodomain inhibition affecting NRF2 regulation is worthy of further mechanistic investigation.…”
Section: Discussionmentioning
confidence: 99%